The Impact of the New Independent Auditor’s Report for the First Year Relative to the Auditing Standards Code 700(Revised) on Audit Fees - Arunruangsirilert, Teerachai; Lertpichate , Totsaporn; Khemmanee, Veerasan (Business Administration and Management Journal Review, 2021)
An auditor’s report is the significant work of an auditor which is a tool to communicate to users of financial statements and provides assurance of the information. However, changed format of a new auditor’s report which has more detail may require more work for the auditor so that it may result increasing of audit fees. This study thus aims explore effect of a changed auditor’s report in the first year following the Thai Standards on Auditing No.700 (Revised) on audit fees. This study uses multiple regression analysis to observe data of firms in SET 100 of the Stock Exchange of Thailand from 2014 to 2016 totally 246 samples. Results show that the new auditor’s report for the first year does not affect audit fees, while size, complexity of business, and loss operating results positively affect audit fees.